DEVELOPMENT AND IMPLEMENTATION OF WOVEN BAMBOO HANDICRAFT ONLINE SHOP IN LOYOK VILLAGE, LOMBOK, INDONESIA - Muhammad Multazam; Eluiz Yansirus Saniyah (Jurnal Techno Nusa Mandiri, 2020)
Lombok Island in Indonesia has been selected as the World's Best Halal Tourism Destination and World's Best Halal Honeymoon Destination in the World Halal Tourism Summit in Dubai 2015 (Khoiriati, 2018). Lombok Island has also been ranked as the Best Halal Travel Destination in Indonesia according to IMTI 2018 and was also named the best halal destination in the international arena in tourism (Ramadhani, 2020). However, the Lombok Earthquake 2018 and the Covid-19 pandemic in 2020 had an impact on Lombok tourism. Loyok village in Lombok as a tourist village that produces woven bamboo crafts is also experiencing marketing problems, namely the decreasing number of sales. In this research, the solution taken in the marketing problem of woven bamboo handicraft products is carried out through the development and implementation of an online shop website. The development method chosen is the waterfall method. System design includes flowchart systems, modeling and database design. In the coding process, the programming language used is PHP 7.0 and MySQL 5.0 database. Implementation has been carried out online and can be accessed via domain anyamandesaloyok.com